Problems of Limiting Cassation in Criminal Cases: Normative Analysis of Article 299 of Law Number 20 of 2025 concerning the Criminal Procedure Code - Muhammad Irfan Fadhila; Fero Sanjaya; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
Law Number 20 of 2025 concerning the Criminal Procedure Code introduces a new policy on limiting cassation remedies in criminal cases through Article 299. The policy is intended to improve judicial efficiency and reduce case backlogs at the Supreme Court. However, the restrictions raise concerns regarding access to justice and the protection of procedural rights within the criminal justice system. This study aims to analyze the normative construction of cassation limitations under Article 299 and examine their implications for the principles of access to justice and fair trial. The research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials are analyzed through grammatical, systematic, and teleological interpretation. The findings reveal that the limitation of cassation reflects a shift in criminal procedural policy from a rights-oriented approach toward an efficiency-oriented approach. Although the policy may contribute to reducing the Supreme Court's caseload, it simultaneously narrows opportunities to correct legal errors and may weaken the cassation function in maintaining uniform application of law. This study argues that cassation limitations should only be applied proportionally and based on clear legal criteria to ensure compliance with due process of law. The research contributes a normative framework for assessing the legitimacy of cassation restrictions by balancing judicial efficiency, legal certainty, and the protection of procedural rights in Indonesia's criminal justice system .   Keywords : Cassation, Limitation of Cassation, Criminal Procedure Code, Supreme Court, Access to Justice, Due Process of Law.